2019
DOI: 10.1016/j.joca.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Exploring longitudinal associations of histologically assessed inflammation with symptoms and radiographic damage in knee osteoarthritis: combined results of three prospective cohort studies

Abstract: s u m m a r yObjective: To explore the associations between different histologically assessed, inflammatory synovial characteristics and subsequent clinical and structural aspects in knee osteoarthritis (OA). Design: Knee OA patients, ranging in stage from early to advanced, were recruited from three different ongoing studies. Synovial tissue biopsies were taken and histologically assessed for six features (four inflammatory related aspects, fibrosis and fibrin deposition). Clinical aspects (WOMAC pain, functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…Additionally, tissue sampling bias may have influenced study results. Prior RA and OA studies suggest that good histologic or RNA sequencing reproducibility can be achieved with 3–4 ultrasound‐guided synovial biopsy samples or with ~150 mg tissue . We found low variability with 4 ~100‐mg OA tissue samples, but we generally used higher tissue amounts to reduce bias.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Additionally, tissue sampling bias may have influenced study results. Prior RA and OA studies suggest that good histologic or RNA sequencing reproducibility can be achieved with 3–4 ultrasound‐guided synovial biopsy samples or with ~150 mg tissue . We found low variability with 4 ~100‐mg OA tissue samples, but we generally used higher tissue amounts to reduce bias.…”
Section: Discussionmentioning
confidence: 70%
“…Many studies have demonstrated heterogeneity in OA synovial responses , reflecting potential differences in disease pathology. To phenotype synovial response patterns in knee OA, we combined ex vivo flow cytometry and multianalyte ELISAs after limited culture of intact tissue (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations